2017
DOI: 10.1007/s10681-017-1942-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity of Patellifolia patellaris from the Iberian Peninsula, a crop wild relative of cultivated beets

Abstract: The genetic diversity of Patellifolia patellaris has been investigated to generate information required for the organisation of a systematic genetic resources conservation action combining the best elements of the ex situ and in situ conservation concept. To this end, ten occurrences of the species were sampled on the Iberian Peninsula in Portugal and Spain. A total of 271 individuals was analysed using 24 microsatellite markers. The factorial analysis separated the material into two occurrences from Portugal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The taxonomic inconsistencies within the subfamily Betoideae have been reported (e.g., Ford-Lloyd, 2005 ; Hohmann et al, 2006 ) repeatedly (see Table 1 ). While the taxonomy of Beta section Beta is settled, uncertainties still exists with respect to section Corollinae and the genus Patellifolia (former Beta section Procumbentes ) (Frese, 2010 ; Frese et al, 2017 ).…”
Section: Cwr For Sugar Beet Improvement: Current Status and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomic inconsistencies within the subfamily Betoideae have been reported (e.g., Ford-Lloyd, 2005 ; Hohmann et al, 2006 ) repeatedly (see Table 1 ). While the taxonomy of Beta section Beta is settled, uncertainties still exists with respect to section Corollinae and the genus Patellifolia (former Beta section Procumbentes ) (Frese, 2010 ; Frese et al, 2017 ).…”
Section: Cwr For Sugar Beet Improvement: Current Status and Prospectsmentioning
confidence: 99%
“…An early diversification between Beta (GP1, GP2) and Patellifolia (GP3) is postulated, and within GP1 and GP2 an ecological divergence between West and East Mediterranean Beta species was identified (Romeiras et al, 2016 ). Also, Frese et al ( 2017 ) assessed genetic diversity in P. patellaris revealing that occurrences from Portugal are genetically different from the Spanish ones (Andrello et al, 2017 ), thus highlighting that Portuguese populations may harbor a different genetic variation that could be associated to the restricted coastal areas where they occur. Several genetic diversity studies in sea beet (e.g., Leys et al, 2014 ; Andrello et al, 2016 ) showed a distribution of genetic diversity according to ecogeographical ranges and, recently, discrimination in Portuguese populations from dissimilar habitats were accomplished (Ribeiro et al, 2016 ).…”
Section: Establishing the Relatedness Between Crops And Cwrmentioning
confidence: 99%
“…The localities were visited by project partners to take plant samples. Further details on the collecting mission are reported by Frese et al (2017b). Information on the geographic origin of the sampled plant species and the material codes used in tables and figures is given in Table 1.…”
Section: Sampling Of Leaf Materialsmentioning
confidence: 99%
“…Furthermore, six occurrences of P. procumbens plus one P. webbiana summing up to a total number of 172 plants were analysed with 22 markers. The descriptor ''population identifier'' and ''site code'' was used in the final report of the GeDiPa project (Frese et al 2017b) and is listed here as a reference. Site codes printed in bold letter indicate the locality of recommended genetic reserves…”
Section: Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation